(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
In this paper, direct numerical simulation (DNS) of spatially evolving flat-plate hypersonic turbulent boundary layer with free-stream Mach number 8 is used to study the effects of wall temperature on compressibility and Reynolds stress contribution. The DNS contains two cases with different wall temperatures, T_w/T_∞=10.03 and 1.9. The results show that lower wall temperature enhances both the compressibility and injection-and-sweeping motions near the wall.